2023
DOI: 10.1093/ve/vead005
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and pandemic spread of small ruminant lentiviruses

Abstract: Small ruminant lentiviruses (SRLVs) cause chronic, persistent infections in populations of domestic sheep (Ovis aries) and goats (Capra hircus) worldwide. The vast majority of SRLV infections involve two genotypes (A and B) that spread in association with the emergence of global livestock trade. However, SRLVs have likely been present in Eurasian ruminant populations since at least the early Neolithic period. Here, we use phylogenetic and phylogeographic approaches to reconstruct the origin of pandemic SRLV st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 56 publications
3
7
0
Order By: Relevance
“…Our results also confirmed the infection of sheep with strains of genotype B, which were initially isolated from goats [50]. This finding is in agreement with previous studies, which reported cross-species transmission of A and B genotype strains between sheep and goats [11][12][13].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results also confirmed the infection of sheep with strains of genotype B, which were initially isolated from goats [50]. This finding is in agreement with previous studies, which reported cross-species transmission of A and B genotype strains between sheep and goats [11][12][13].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, the other group of gag-pol sequences was clearly clustered with B2 strains isolated in Italy and Spain [7,[46][47][48], presenting very low values of nucleotide distance (<10%) as derived from the nucleotide pairwise comparisons. The genetic association of SRLV strains of genotypes A and B with these specific regions is consistent with previous phylogenetic studies indicating the Middle East and Central Europe as the ancestral regions of the A and B genotypes, respectively [49,50]. Nevertheless, further investigation and bioinformatics analyses of whole-genome sequence data are imperative for the exploration of the origin of SRLV strains isolated in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…The first belonged to the B2 subtype, firstly isolated in cases of arthritis in Spanish sheep [51,52] and now endemic in Mediterranean flocks without species restrictions [25,26,37,40,[53][54][55][56]. However, the majority of sequences retrieved in the study were clustered in a new A subgroup closely related to previously reported Greek and Lebanese sequences [6,57]. These sequences showed a mean genetic distance from around 13.6 to 15.8% with the A12 Polish sequence and, based on the SRLV classification reported by Shah [3], can be tentatively assigned to a new A28 viral subtype.…”
Section: Discussionsupporting
confidence: 55%
“…It should be noted that only two sequences of small ruminant lentiviruses isolated in the Russian Federation are available in Genbank (MN186380.1-Mordovia 2018; JN008914.1-Tverskoy 2008). Due to the high variability of the genomes of lentiviruses, their phylogenetic analysis is complicated [46].…”
Section: Discussionmentioning
confidence: 99%